Esophageal motor disorders in older adults: experience with highresolution esophageal manometry at a referral center in Colombia - Hani, Albis (2025)
Introduction: Advanced age is associated with a greater prevalence of oesophageal motor disorders due to increased lower oesophageal sphincter (LES) pressure and decreased peristaltic vigour. Secondary peristalsis is particularly affected by age, which may be related to increased oesophageal dysmotility in older adults. Objectives: To describe the most common oesophageal disorders in older adults undergoing high-resolution oesophageal manometry (HREM) according to the Chicago Classification V4.0. Materials and methods: An observational, descriptive, retrospective, cross-sectional study was conducted at San Ignacio University Hospital. Patients over 65 years of age who underwent HREM for various reasons between 2020 and 2025 were included. Results: Total number of patients included, age and age range. A total of 177 patients aged 65 years or older, with an age range of 68- 76 years, were included. The main indication for HREM was dysphagia, present in 49.7% of patients, followed by reflux symptoms in 39%. The most frequent pathological manometric diagnosis was inconclusive outlet obstruction (14.1%), followed by ineffective oesophageal motility (9.6%) and achalasia (5.1%). A manometric diagnosis of ineffective oesophageal motility was made in 17.1% of patients with erosive gastro-oesophageal reflux disease (GERD). Conclusion: Older adults are more likely to have esophageal dysmotility, and outflow tract obstruction disorders are the most frequently identified in this population.